2012
DOI: 10.1002/ijc.27726
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of p53 in the cytotoxic activity of the NAMPT inhibitor FK866 in myeloid leukemic cells

Abstract: FK866 is a specific inhibitor of NAMPT and induces apoptosis of leukemic cells by depletion of intracellular NAD+. Since up-regulation of NAMPT is associated with several cases of cancers, including leukemias, we asked whether in leukemic cells inhibition of NAMPT involves p53 pathway. We observed that FK866 induced apoptosis and reduced cell proliferation in NB-4, OCI-AML3 and MOLM-13 cell lines. In contrast, the leukemia cell lines, K-562 and Kasumi, containing nonfunctional p53 were relatively unaffected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 60 publications
(120 reference statements)
6
40
1
Order By: Relevance
“…Break down of ATP levels was associated with increased cell death. In contrast to another study [6], we demonstrated that FK866 reduced NAMPT activity, depleted NAD and ATP content and induced cell death in p53-deficient Hep3B cells suggesting that FK866-mediated cell death does not depend on functional p53. Our results are in line with a study performed in chronic lymphocytic leukemia cells [14].…”
Section: Discussioncontrasting
confidence: 82%
“…Break down of ATP levels was associated with increased cell death. In contrast to another study [6], we demonstrated that FK866 reduced NAMPT activity, depleted NAD and ATP content and induced cell death in p53-deficient Hep3B cells suggesting that FK866-mediated cell death does not depend on functional p53. Our results are in line with a study performed in chronic lymphocytic leukemia cells [14].…”
Section: Discussioncontrasting
confidence: 82%
“…While Nahimana et al reported an EC 50 value of 7.2 nM using the MTT assay, 18) Thakur et al found no inhibition at 100 nM using the trypan blue exclusion assay. 19) Here, we showed that FK866 inhibits K562 cell growth with high potency using the WST-8 assay, which is similar to the MTT assay. This discrepancy in findings may be due to differences in the mode of measurement.…”
Section: Discussionsupporting
confidence: 61%
“…We confirmed that FK866 did indeed inhibit K562 cell growth using a DNA content-based assay (data not shown). 19) We demonstrated that our hit compounds reduced NAD content in the cytoplasm to about 60% of baseline levels at 5 h after addition of hit compounds and FK866. Previous studies showed time-dependent decreases in NAD induced by FK866 in THP-1 and other cells, 12,17) and our data showed that caspase 3/7 activation in THP-1 occurred after 24 h (data not shown), suggesting that apoptosis was caused by NAD depletion.…”
Section: Discussionmentioning
confidence: 70%
“…156 Cancer cells are more susceptible to NAMPT inhibition than normal cells. 157,158 Clinical studies have demonstrated that serum or blood levels of eNAMPT are increased in patients with cancer and a positive correlation exists between either tissue or eNAMPT levels and the stage of cancer progression. [159][160][161][162][163] However, the molecular pathways of eNAMPT signalling in carcinogenesis are far from clear.…”
Section: Nampt In Cancermentioning
confidence: 98%